PENGARUH PENGGUNAAN MEDIA SOSIAL WHATSAPP TERHADAP KEAKTIFAN SISWA PADA MATA PELAJARAN EKONOMI BISNIS KELAS X SMK NEGERI 2 BOYOLANGU TAHUN AJARAN 2018/2019 - mega wigas widhiya; Nailariza Umami; Imam Sukwatus Suja’I (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2019)
Research this discuss about use social media influence WhatsApp to activity students in learning economy the business. Study this on the background backwards by the amount students who use social media WhatsApp on their smartphones and always bring it everywhere they go including in the environment school. The research aims to find out whether or not the influence of social media WhatsApp to the activity students in economy the business learning. This is experiment research with pre-experimental method and uses pre-test post-test research design. The subject research is students in X-class banking 2 SMKN 2 Boyolangu this sample taken based on the cluster sample. The research uses the instrument of observation. In class, this data taken before and after treatment where the materials given at learning to use the application WhatsApp. Technique analysis hypothesis use a sign test obtained results p 0,021 ≤ α 0,025 and Zcount amount to 2,309 > Ztable amount to 1.96, so H0 is rejected and Wilcoxon matched pairs with obtained results p = 0,021 ≤ α = 0,025 and Zcount amount to 2.827 > Ztable amount to 1.96, then H0 is rejected. Thus in this research stated there is the influence of social media WhatsApp use to activity learn students X-class banking 2 on the learning of economics the business.